Unexpected findings in the Eocene Baltic amber forests: Ground beetle fossils of the tribe Nebriini (Coleoptera: Carabidae) - Schmidt, Joachim; Scholz, Stefan; Kavanaugh, David H. (Zootaxa, 2019)
Occurrence of the ground beetle tribe Nebriini in the Baltic amber forest is confirmed. The nebriine taxon Archaeonebria inexspectata gen. n., sp. n., is described and imaged based on four fossil specimens preserved in the Eocene Baltic amber using light microscopy and X-ray micro-computed tomography. The new taxon shares likely synapomorphies with the amphipacific genus Nippononebria and is therefore proposed as its sister group. The occurrence of Archaeonebria in the Baltic amber forests supports previous assumptions that these forests grew under temperate, at least warm-temperate, climatic conditions.